Answer:
b. circle; ![2(x')^2+2(y')^2-5x'-5\sqrt{3}y'-6 =0](https://tex.z-dn.net/?f=2%28x%27%29%5E2%2B2%28y%27%29%5E2-5x%27-5%5Csqrt%7B3%7Dy%27-6%20%3D0)
Step-by-step explanation:
The given conic has equation;
![x^2-5x+y^2=3](https://tex.z-dn.net/?f=x%5E2-5x%2By%5E2%3D3)
We complete the square to obtain;
![(x-\frac{5}{2})^2+(y-0)^2=\frac{37}{4}](https://tex.z-dn.net/?f=%28x-%5Cfrac%7B5%7D%7B2%7D%29%5E2%2B%28y-0%29%5E2%3D%5Cfrac%7B37%7D%7B4%7D)
This is a circle with center;
![(\frac{5}{2},0)](https://tex.z-dn.net/?f=%28%5Cfrac%7B5%7D%7B2%7D%2C0%29)
This implies that;
![x=\frac{5}{2},y=0](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B5%7D%7B2%7D%2Cy%3D0)
When the circle is rotated through an angle of
,
The new center is obtained using;
and ![y'=-x\sin(\theta)+y\cos(\theta)](https://tex.z-dn.net/?f=y%27%3D-x%5Csin%28%5Ctheta%29%2By%5Ccos%28%5Ctheta%29)
We plug in the given angle with x and y values to get;
and ![y'=--(\frac{5}{2})\sin(\frac{\pi}{3})+(0)\cos(\frac{\pi}{3})](https://tex.z-dn.net/?f=y%27%3D--%28%5Cfrac%7B5%7D%7B2%7D%29%5Csin%28%5Cfrac%7B%5Cpi%7D%7B3%7D%29%2B%280%29%5Ccos%28%5Cfrac%7B%5Cpi%7D%7B3%7D%29)
This gives us;
![x'=\frac{5}{4} ,y'=\frac{5\sqrt{3} }{4}](https://tex.z-dn.net/?f=x%27%3D%5Cfrac%7B5%7D%7B4%7D%20%2Cy%27%3D%5Cfrac%7B5%5Csqrt%7B3%7D%20%7D%7B4%7D)
The equation of the rotated circle is;
![(x'-\frac{5}{4})^2+(y'-\frac{5\sqrt{3} }{4})^2=\frac{37}{4}](https://tex.z-dn.net/?f=%28x%27-%5Cfrac%7B5%7D%7B4%7D%29%5E2%2B%28y%27-%5Cfrac%7B5%5Csqrt%7B3%7D%20%7D%7B4%7D%29%5E2%3D%5Cfrac%7B37%7D%7B4%7D)
Expand;
![(x')^2+(y')^2-\frac{5\sqrt{3} }{2}y'-\frac{5}{2}x'+\frac{25}{4} =\frac{37}{4}](https://tex.z-dn.net/?f=%28x%27%29%5E2%2B%28y%27%29%5E2-%5Cfrac%7B5%5Csqrt%7B3%7D%20%7D%7B2%7Dy%27-%5Cfrac%7B5%7D%7B2%7Dx%27%2B%5Cfrac%7B25%7D%7B4%7D%20%3D%5Cfrac%7B37%7D%7B4%7D)
Multiply through by 4; to get
![4(x')^2+4(y')^2-10\sqrt{3}y'-10x'+25 =37](https://tex.z-dn.net/?f=4%28x%27%29%5E2%2B4%28y%27%29%5E2-10%5Csqrt%7B3%7Dy%27-10x%27%2B25%20%3D37)
Write in general form;
![4(x')^2+4(y')^2-10x'-10\sqrt{3}y'-12 =0](https://tex.z-dn.net/?f=4%28x%27%29%5E2%2B4%28y%27%29%5E2-10x%27-10%5Csqrt%7B3%7Dy%27-12%20%3D0)
Divide through by 2.
![2(x')^2+2(y')^2-5x'-5\sqrt{3}y'-6 =0](https://tex.z-dn.net/?f=2%28x%27%29%5E2%2B2%28y%27%29%5E2-5x%27-5%5Csqrt%7B3%7Dy%27-6%20%3D0)
Answer:
6√2
Step-by-step explanation:
A 45 45 90 right triangle, so ratio of leg : leg: hypotenuse = a: a : a√2 (a = value of leg)
Given: leg = 6
So the ratio of leg : leg: hypotenuse = 6 : 6 : 6 √2
Answer:
x = 6√2
Answer:
<h2>V = 27m³</h2>
Step-by-step explanation:
We know: All faces of a cube are squares.
The formula of an area of a square with a side <em>s</em>:
<em>A = s²</em>
We have <em>A = 9m²</em>
Substitute:
<em>s² = 9 → s = √9 = 3 m</em>.
The formula of a volume of a cube with an edge <em>s</em>:
<em>V = s³</em>
Substitute:
<em>V = 3³ = 27 m³</em>
Answer:
There is an incompletion here
"FOUND THAT THE --------- IS 58
Step-by-step explanation:
Answer:
15
Step-by-step explanation: